Analyzing digital resilience strategies for Harian Waspada through ANP and Maqashid Shariah in a VUCA environment - Arsyadona, Arsyadona; Rokan, Mustapa Khamal; Rahmani, Nur Ahmadi Bi (Journal of Islamic Economics Lariba, 2025)
IntroductionPrint media organizations in Indonesia face mounting pressure as digital technology reshapes audience behavior, advertising markets, and competition. Harian Waspada, a long-standing Sharia-based newspaper, must navigate an environment defined by volatility, uncertainty, complexity, and ambiguity while preserving its ethical foundation. The organization confronts declining print revenue, limited digital capability, and evolving expectations for interactive and diverse content. These challenges call for a comprehensive assessment of how financial, technological, organizational, and ethical dimensions shape long-term resilience.ObjectivesThis study aims to identify the most critical factors that influence the resilience of Harian Waspada in the digital era and to determine strategic priorities that support sustainable transformation. It also seeks to explore how principles of Maqashid Shariah can guide responsible decision-making and strengthen adaptability in a rapidly changing media landscape.MethodThe study employed a mixed-methods approach. Qualitative insights were collected through interviews with individuals who understand the newspaper’s operations and the broader media industry. Quantitative analysis was conducted using the Analytic Network Process to examine the relationships among financial sustainability, digital readiness, organizational culture, audience engagement, and ethical considerations. The analysis produced priority rankings and illustrated the interdependence among these factors.ResultsThe findings show that financial sustainability and digitalization challenges present the greatest obstacles to organizational resilience. A substantial decline in advertising revenue, combined with limited technological infrastructure and digital skills, restricts the pace of transformation. The study also reveals that audience engagement, content diversification, and stronger internal coordination are essential for long-term survival. Strategic priorities include investment in digital technology, enhancement of human resources, development of interactive communication channels, and content innovation. Ethical guidance derived from Maqashid Shariah supports the creation of responsible journalism and strengthens trust with readers.ImplicationsThe results indicate that successful adaptation requires a holistic approach that aligns technological advancement, financial management, organizational transformation, and ethical values. Strengthening the connection between strategic planning and Maqashid Shariah encourages balanced growth and reinforces the social role of the media.Originality/NoveltyThis study offers an integrative perspective by combining the Analytic Network Process with Maqashid Shariah to evaluate media resilience. It provides a structured framework that connects digital transformation, financial stability, organizational renewal, and ethical governance in an Islamic media context.